Pengaruh Penerapan Good corporate governance Terhadap Nilai Perusahaan: Sebuah Literatur Review - Widy Muchamad; Lena Agustin (ECONEUR (Journal of Economics and Entrepreneurship), 2023)
This study aims to analyze the effect of good corporate governance (GCG) on company value through a literature review using a literature search in several electronic sources, including Google Scholar, Scopus, ScienceDirect and ACM Digital Library. Data obtained from 11 available studies (full text) published starting from 2018-2023. The results of the literature review show that the implementation of good corporate governance (GCG) partially and simultaneously has an influence on firm value.